2013
DOI: 10.1111/jcpt.12068
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the costs of paediatric antibiotic prescribing in the community by implementing guideline recommendations

Abstract: This is the first Italian study to evaluate the costs related to a specific prescription profile, which already exists in the real setting, hypothesizing its application in a large outpatient child population of the same geographical area. The results show that by improving prescribing appropriateness, it is possible to reduce the expenditure associated with antibiotic prescriptions to outpatient children in the Lombardy region by about one-fifth. The lower rate of hospital admissions for ARI suggests that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 28 publications
4
12
1
2
Order By: Relevance
“…ISG has a significant impact on reducing the average cost of drug prescription per patient with respiratory disease because of the decrease in the cost of antibiotics and adjuvant useless drug prescriptions. Similar results were reported in the studies of Piovani et al and the Path-Theta Collaboration [18,25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…ISG has a significant impact on reducing the average cost of drug prescription per patient with respiratory disease because of the decrease in the cost of antibiotics and adjuvant useless drug prescriptions. Similar results were reported in the studies of Piovani et al and the Path-Theta Collaboration [18,25].…”
Section: Discussionsupporting
confidence: 91%
“…The findings of our study highlight a significant decrease in drug prescription in general and in antibiotic prescription in particular. Similar results were reported when guidelines were used for prescription of antibiotics [15][16][17][18]. Although ISG reduced antibiotic use for respiratory infections by half in Fiji, it did not alter prescription patterns in an Ugandan study.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17] Our study chose urology as the entry point, and it shows that pharmacist intervention on antibiotic use and prophylactic antibiotic use for clean operations is effective. [11][12][13][14][15][16][17] Our study chose urology as the entry point, and it shows that pharmacist intervention on antibiotic use and prophylactic antibiotic use for clean operations is effective.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that pharmacists could play an important role in the responsible use of antibiotics. [11][12][13][14][15][16][17] Our study chose urology as the entry point, and it shows that pharmacist intervention on antibiotic use and prophylactic antibiotic use for clean operations is effective. Pharmacists participating in antibiotic stewardship programmes can promote the responsible antibiotic use and decrease costs while improving such use.…”
Section: Discussionmentioning
confidence: 99%